The historical context of agriculture in Brazil and the awakening of agroecological movements aiming at more sustainable agricultural systems - Arruda, Emanuelle Lemos de (2022)
The present work consists of a historical journey from the specialized bibliography that seeks to contextualize the history of agriculture in Brazil in order to understand the emergence of agroecological movements for more sustainable agricultural systems. Both productions intended for export and domestic trade were carried out in a traditional way, which means that it was a production with little technological use. In 1960, there is a successive demand for food and other products, thus initiating a process of modernization called the Green Revolution, a period marked by the modernization of agriculture, responsible for livestock and agricultural changes. Since then, there have been several groups opposing the new model of agriculture, based on the use of pesticides and the practice of deforestation. In Brazil, one of these prominent protesting groups was that of alternative agriculture, subsequently encouraging the emergence of Agroecology. With the growing number of adepts of Agroecology, other sister currents were emerging in Brazil, highlighting Organic Agriculture, Natural, Permaculture and Biodynamic Agriculture. The growing awareness of society, boosted by agroecological movements, reveals the problems inherent to so-called conventional agriculture, which has caused environmental damage that is not always measurable. There are many obstacles to be faced, one of them is the reduction in the use of pesticides. Therefore, it is more than necessary that there be political changes, but also of a social nature, seeking to broaden the discussion on agribusiness, the use of machinery, pesticides and synthetic fertilizers in food production.